Sobre um Sistema do tipo Schrödinger-Poisson - Batista, Alex de Moura (2012)
In this dissertation, we study the existence of two types of non-negative weak solutions for a class of problems of Schrodinger-Poisson type. This kind of problem models, for example, several physical phenomena in quantum mechanics. Initially, by minimization arguments, Splitting Lemma and the Variational Principle of Ekeland we find a weak solution that minimizes the minimum energy level associated to the variety of Nehari N. This is the so-called ground state solution. Afterwards we will find, by using the Linking Theorem, a strictly positive weak solution which is not a ground state solution: the so-called bound state solution.